Bilio-Cutaneous fistula and cholecisto- digestive double fistula in a regastrectomized patient due to gastric cancer - Praderi, José; Terra, Eneas; Cassinasco, Angeles; Curuchet, Eduardo; Palacio, José; Praderi, Raúl (Cirugía del Uruguay, 1989)
. A re-gastrectomized patient because of cancer of the gastric stump presented a cholecisto-colonic double fistula preceded by a biliar ileus and obstruction by an intraluminal foreign body that was treated with colonic delivery. Later the patient prsented a cholecistocutaneous fistula; biliar stones appeared through it, which made diagnosis possible. Double biliar fistulas are uncommon, and triple ones such as this case are exceptional.